Equality within our lifetimes : how laws and policies can close-or widen-gender gaps in economies worldwide - Heymann, Jody, 1959-; Sprague, Aleta, 1986-; Raub, Amy, 1981- (University of California Press, 2023)
"The book proceeds in three sections. In section one, we examine how the laws in every country address discrimination in the workplace-not only on the basis of sex and gender, but also based on pregnancy, family status, race/ethnicity, religion, disability, migration status, sexual orientation, socioeconomic status, and gender identity. Section 2 explores why achieving gender equality in the economy will be impossible without addressing both paid and unpaid caregiving. Lastly, in section three, we assess what it takes to make change happen. Section three examines approaches that would make a difference within months as well as approaches that would be transformational long-term"--